Conceptual model of sport-specific classification for para-athletes with intellectual impairment - Van Biesen, D.; Burns, J.; Mactavish, J.; Van de Vliet, P.; Vanlandewijck, Y. (Journal of Sports Sciences, 2021)
The present paper describes the conceptual basis of evidence-based classification of para-athletes with intellectual impairment (II). An extensive description of the theoretical and conceptual foundation of the system as currently conceived is provided, as are examples of its applications in the three sports included in the Paralympic programme for II-athletes in 2020 (i.e., athletics, swimming and table tennis). Evidence-based classification for II-athletes is driven by two central questions: i. How can intellectual impairment be substantiated in a valid and reliable way, and ii. Does intellectual impairment limit optimal sport proficiency? Evolution of the system and current best practice for addressing these questions are described, and suggestions for future research and development are provided. Challenges of understanding and assessing a complex (multifaceted and intersectional) impairment in the context of sport also are considered.